Proudění kapaliny mezi dvěma paralelními deskami, srovnání měření a analytického řešení. - Kárník, Jan (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2013)
Tato diplomová práce je zaměřena na měření rychlostních profilů v kapalinách pomocí ultrazvuku. V práci je popsána dvojice provedených měření jednak v kanále s volnou hladinou, jednak v potrubí čtvercového průřezu. Úvodem se práce zabývá objasněním teoretických základů souvisejících s měřením metodou UVP jako jsou Dopplerův jev, rychlost zvuku v médiu či akustická impedance prostředí. V další části je popsána exekuce měření rychlostního profilu v kanále s volnou hladinou a popis výsledků dosažených při tomto měření. V poslední části se diplomová práce zabývá měřením rychlostního profilu v potrubí čtvercového průřezu. Dále je zde provedeno srovnání výsledných naměřených rychlostních profilů s rychlostními profily stanovenými analytickým vztahem. Závěrem je provedeno zhodnocení dosažených výsledků.

This master's thesis is focused on measurement of the velocity profiles in liquids using ultrasound. The thesis describes two executed measurements both in the channel with free surface, both in the square shaped pipe. In the introductory part this work deals with clarifying the theoretical fundamentals associated with the measurement method UVP such as the Doppler effect, the speed of sound in the medium or the acoustic impedance of the environment. The next part describes the execution of the velocity profile measurement in the channel with free surface described and there is also the description of the results achieved during this measurement. In the last part the thesis deals with the measurement of the velocity profile in the square shaped pipe. There is also the comparison between the measured velocity profiles and the velocity profiles calculated using the analytical formula. In the conclusion there is the evaluation of achieved results.
The Fluid Flow Between Two Paralel Plates, the Comparison Between the Measruring and The Analytical Solution.
Keywords: měření; rychlostní profil; ultrazvuk; ultrasound velocity profile; UVP; measurement; ultrasound; velocity profile; ultrasound velocity profile; UVP